Penerapan Prinsip Bioetika dalam Pemeriksaan Kualitas Air (Pb dan Cd) dengan Metode AAS (Atomic Absorption Spectro-Photometer): (Studi Kasus di UPT Laboratorium Pengujian Mutu dan Keamanan Pangan Kota Medan) - Nita Maya Sari Pane; Zihan Zahriani Batubara; Ahmad Shafwan Pulungan; Nurbaity Situmorang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Current water safety issues in society are very diverse. Water quality safety issues are closely related to the bioethics of water testing, because water testing involves protecting human health and the environment. Water quality testing is an important part of ensuring that the water consumed is safe for human health. The purpose of this study was to evaluate the application of bioethical principles in water quality testing (Pb and Cd). This study was conducted in March 2025 at the UPT Food Security Laboratory of Medan City. The data analysis used in this study used qualitative descriptive methods to see the pattern of observation responses. The results of the study showed that in the bioethical aspect of sample testing, analysts who conducted the testing had implemented bioethics or SOPs that apply in food quality and safety testing laboratories. In conducting water testing for lead and cadmium examination, the procedures used were in accordance with applicable requirements using testing procedures from SNI (Indonesian National Standard).